Pengaruh Fear Of Missing Out Dan Brand Trust Terhadap Keputusan Pembelian Produk The Originote: (Studi Pada Mahasiswa Program Studi Manajemen Fakultas Ekonomi Dan Bisnis Universitas Negeri Makassar) - Nur Wahida; Burhanuddin Burhanuddin; Muhammad Ilham Wardhana Haeruddin; Muhammad Ichwan Musa; Annisa Paramaswary Aslam (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
Consumer preferences and strengths have undergone significant changes with the advancement of technology, and intense market competition necessitates companies to be more competitive, particularly in their marketing activities. To endure amidst the highly competitive market, companies need to delve into consumer behavior to implement appropriate strategies. The Fear of Missing Out (FOMO) and Brand Trust behaviors in consumers are influential factors that can drive them to make purchasing decisions. This research aims to determine the impact of Fear of Missing Out and Brand Trust on the purchasing decisions of The Originote products. It is a quantitative study with a descriptive approach. The sample comprises 100 students from the Management Program at the Faculty of Economics and Business, Universitas Negeri Makassar. Data collection is carried out through observation, literature review, and surveys. Data analysis is conducted using multiple regression analysis with Statistical Product and Service Solution (SPSS). The research results indicate that Fear of Missing Out and Brand Trust simultaneously have a positive effect on purchasing decisions. Furthermore, Fear of Missing Out has a positive but not significant impact on purchasing decisions, while Brand Trust has a positive and significant influence on purchasing decisions..